Spousal Concordance of Diabetes Mellitus among Women in Ajman, United Arab Emirates - Al-Sharbatti, Shatha S. (Sultan Qaboos Univ Med J, 2016)
OBJECTIVES: Spousal concordance is defined as similar behaviours and associated health statuses between spouses. This study aimed to identify the concordance of diabetes mellitus (DM) and related variables among genetically unrelated couples in Ajman, United Arab Emirates (UAE). METHODS: This cross-sectional study included 270 married women attending either the Mushairef Health Center or the Gulf Medical College Hospital in Ajman between May and November 2012. A validated questionnaire was designed to determine sociodemographic characteristics and a history or family history of DM, hypertension, coronary artery disease or dyslipidaemia among the women and their husbands. The weight, height, body mass index, waist circumference, fasting blood sugar and glycated haemoglobin (HbA1c) levels of all women were measured. RESULTS: Of the women, 39.3% of those with diabetic husbands and 39.9% of those with non-diabetic husbands were diabetic themselves (P >0.050). The prevalence of DM spousal concordance was 17.8%. A history of hypertension, coronary artery disease and dyslipidaemia was significantly more frequent among women whose husbands had a history of the same conditions (P = 0.001, 0.040 and 0.002, respectively). Spousal concordance of abnormal glycaemia among non-diabetic women with diabetic husbands was significant (P = 0.001). Having a diabetic husband (P = 0.006) and being obese (P = 0.009) were the only significant predictors of hyperglycaemia among non-diabetic women after controlling for confounding factors. CONCLUSION: There was significant concordance of abnormal glycaemia among non-diabetic women with diabetic husbands. The spouses of diabetic patients may therefore be a target population for regular hyperglycaemia and DM screening.